STUDENTS’ ATTITUDE TO ENGLISH SUMMATIVE AND FORMATIVE ASSESSMENT AT THE EIGHTH GRADE STUDENTS OF MTs HUBBULWATHAN DURI - zulfia siskawati; Irma Nola Sari (STAI Hubbulwathan Duri, 2018)
Penelitian ini bertujuan untuk mengetahui sikap siswa terhadap penilaian sumatif dan formatif bahasa Inggris pada siswa kelas VIII MTs Hubbulwathan Duri, tahun ajaran 2017/2018. Jenis penelitian ini adalah penelitian survei yang menggunakan angket untuk mengumpulkan data. Angket tersebut terdiri dari 30 pernyataan yang berkaitan dengan sikap siswa terhadap penilaian sumatif dan penilaian formatif. Subjek penelitian ini adalah siswa kelas VIII MTs Hubbulwathan Duri. Ada 75 siswa sebagai sampel. Berdasarkan analisis data, peneliti menemukan bahwa sikap siswa bervariasi pada kedua komponen. Total rata-rata jawaban siswa 69.16% pada penilaian sumatif dan 78.54% pada penilaian formatif. Berdasarkan hasil penelitian, ini menunjukkan bahwa sikap siswa terhadap penilaian sumatif dan formatif di kelas VIII MTs Hubbulwathan Duri adalah tinggi.This research was aimed to find out the students’ attitude to English summative and formative assessment at the eighth grade students of MTs Hubbulwathan Duri, in the academic year 2017/2018. The type ofthe research was survey research which used questionnaire to collect the data. The questionnaire consisted of 30 items dealing with students’ attitude to summative and formative assessment. The subject of this research was the eighth grade students of MTs Hubbulwathan Duri. There were 75 students as sample. Based on the data analysis, the researcher found that the students’ attitude had various numbers for each component. The total mean of students’ answer was 69.16% in summative assessment and 78.54% in formative assessment. Based on the research finding, it shows that the students’ attitude to English summative and formative assessmentat the eighth grade of MTs Hubbulwathan Duri was high